A new species of six-gilled hagfish (Myxinidae: Eptatretus) from the Lakshadweep Sea - Augustina A.x., Treasa; Sreeram, Miriam Paul; Sukumaran, Sandhya; K.m., Sreekumar; Jose, Anjaly; K.k., Joshi; A., Gopalakrishnan (Zootaxa, 2022)
A new species of hagfish, Eptatretus wadgensis sp. nov., is described from the Wadge Bank, Lakshadweep Sea, India, obtained from a depth of ~250–300 m through deep-sea trawling. It is diagnosed by having six pairs of gill pouches and gill apertures, 3/3 multicusp teeth, total slime pores 67–69, six branchial slime pores, and ventral aorta bifurcating at the 4th or between 4th and 5th gill pouch. The new species has significant morphological differences in total dental cusps, total slime pores, body proportions and the absence of the nasal-sinus papilla when compared to congeners and formed a distinct clade in phylogenetic reconstruction and a genetic distance of 3.41–4.00% when comparing K2P parameters with the nearest species. A key to the Eptatretus species of the Indian Ocean is provided.